(3GdHfhc heMGaX GdESJKeGQ (B:s (3eONd OYe GJNGP GdbQGQ (B/s - (3OGhO, Ydj SYO eMeOs ((3GdEScfOQjI(B: s (3OGQ GdJYdje GdLGeYj(B, s, 2012)
(3GdHfhc, eGgjI GdHfhc hhXGFagG GdCSGSjI(B- (3bjGS JcdaI GdCehGd hJSYjQ GdhOGFY hGdbQhV GdeUQajI(B- (3EOGQI GdSjhdI hedGFeI QCS GdeGd ddHfhc(B- (3Jbjje COGA GdHfhc(B- (3GdCSGdjH GdcejI aj GdHfhc(B- (3eMGaX GdESJKeGQ(B- (3CShGb GdeGd GdCOhGJ hGdeDSSGJ(B- (3eDTQGJ GdHhQUI(B- (3EOGQI eMGaX GdChQGb GdeGdjI(B- (3JMdjd hJbjje GdCSge hGdSfOGJ(B- (3EfJbGA GdeMaXIs
Keywords: (3EJNGP GdbQGQGJ(B- (3GdEOGQIs; (3GdESJKeGQs; (3GdHfhcs; (3GdHfhc(B- (3JfXje hEOGQIs